005.5 Treponema pallidum strain-types in australia and association with macrolide resistance. (13th September 2015) - Read, P; Tagg, K; Jeoffreys, N; Gilbert, G; Guy, R; Donovan, B
Abstract : Introduction: Greater understanding of the molecular epidemiology of Trepomema pallidum has the potential to enhance control measures. The aim of this study was to determine the strain-types of T. pallidum in Sydney, Australia, and investigate clinical and epidemiological associations. Methods: Stored T. pallidum DNA from samples between 2004–2011were catagorised into strain-types using analysis of the acidic repeat protein (arp), T.pallidum repeat sub- family (tpr) genes, and sequence analysis of the TP0548 gene as described by Marra (2010). Associations between strain-type, the macrolide resistance mutation A2058G, and clinical and demographic characteristics were further investigated. Results: 194 samples from 187 patients were successfully strain-typed into at least 19 separate strains. The predominant strains were 14d/g (91/194; 47%), and 14d/f (18/194; 9%).14d/g remained the commonest strain throughout the study period, and was associated with the A2058G mutation (90/91 vs 70/103 non-14d/g strains: OR 42.4; 95% CI 5.7–317.9 p < 0.001). Clinical information was available for 91 samples. 90 were male, of whom 89 reported sex with other men. 21/48 (44%) strains from HIV negative patients were strain 14d/g vs 20/43 (47%) from those HIV positive (OR 1.1; 95% CI 0.5–2.5 p = 0.79). When acquisition was reported as being outside Australia 2/13 (15%) cases were strain 14d/g vs 39/78 (50%) of those reporting sex only within Australia (OR 0.18; 95% CI 0.04–0.87 p = 0.033.) Both cases of neurosyphilis were attributable to TP0548 gene sequence "f". Conclusion: This is the first time that enhanced strain-typing has been used to define the epidemiology of Treponema pallidum infections in the Asia-Pacific region. The most common strain (14d/g) was associated with macrolide resistance and acquisition within Australia. Despite the diversity of strains, the lack of association with HIV status suggests sexual networks between HIV negative and HIV positive men overlap. Disclosure of interest statement: Phillip Read received an RACP Novartis Sexual Health Research Scholarship to part fund this research.